Symilarity of standards and models according to risk management process for software development (2012)
In this paper we present an analysis of similarities between standards and models that consider the risk management in the software development area. This analysis is based on a method designed to establish similarities between standards and models, which has been validated by the Universidad Politécnica de Madrid. The research presented here is part of a project carried out at the Universidad de Medellín (Colombia) and Universidad Católica del Norte (Chile). Development of this project was made with the support of an expert group composed by professional software developers, researchers and software engineers. © 2012 AISTI.